Philological and historical commentary on Ammianus Marcellinus XXVIII - Boeft, J. den. (Philological and Historical Commentary on Ammianus Marcellinus, 2011)
In Book 28 Ammianus describes the military activity of Valentinian on the Rhine. The historian speaks with admiration about his efforts to strengthen the northwestern border of the empire. He shows a similar esteem for the general Theodosius, who re-established order in Britain. However, in the greater part of Book 28 there is an air of gloom. Ammianus writes reluctantly about the judicial terror inflicted on the Roman aristocracy by powerful magistrates. In his digression about Roman manners he speaks with contempt about the senatorial elite and the Roman plebs, because they fail to live up to the standards of their ancestors. The final chapter illustrates the disastrous effects of the mismanagement of the province of Tripolis by corrupt officials.